Tingkat risiko bencana tanah longsor di Kecamatan Tirtomoyo, Kabupaten Wonogiri - Mutiara Riska Ramadhani; Galing Yudana; Nur Miladan (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Tirtomoyo Sub-district in Wonogiri Regency has relatively high and increasing frequency of landslide disasters. This condition is influenced by the area’s physical characteristics, dominated by hilly terrain, high rainfall intensity, and human activities on slopes that increase disaster vulnerability. Landslide events have caused significant impacts, particularly on infrastructure damage and socio-economic activities. This study aims to assess landslide disaster risk levels in Tirtomoyo Sub-district as a basis for disaster-informed regional development planning. A deductive approach with quantitative methods is employed, utilizing scoring and weighting techniques combined with spatial overlay analysis. The study uses physical environmental data and relevant socio-economic data. The results indicate that Tirtomoyo Sub-district is classified into safe zones and landslide risk zones with low, moderate, and high risk levels. Landslide hazard levels are influenced by slope gradient, lithology, soil type, rainfall, and land cover, with the study area predominantly characterized by moderate hazard levels. Meanwhile, vulnerability assessment based on social, physical, and economic aspects shows that the area is generally dominated by low vulnerability. The interaction between hazard and vulnerability factors generates varying levels of landslide risk across the study area. These findings provide important insights for disaster mitigation strategies and support the development of more adaptive and sustainable regional planning in Tirtomoyo Sub-district.